تقييم أعضاء هيئة التدريس في مجال الإعلام لجودة العملية التعليمية في التعليم العالي في ظل جائحة كورونا COVID-19 - سالم، دعاء فتحي سالم (جامعة القاهرة - كلية الإعلام - مركز بحوث الرأي العام, 2020)
هدفت الدراسة الحالية إلى التعرف على تقييم أعضاء هيئة التدريس في مجال الإعلام بالجامعات المصرية لجودة العملية التعليمية في التعليم العالي في ظل جائحة كورونا 19-C0VID، التعرف على أهم المنصات التعليمية التي تم استخدامها أثناء جائحة كورونا، رصد التحديات التي تم مواجهتها أثناء القيام بالتعليم عن بعد، الوصول إلى صياغة معايير مقترحة للتعليم عن بعد خاصة بالتعليم العالي في الجامعات المصرية، وتمثلت عينة الدراسة في أساتذة الإعلام بجامعة القاهرة والمنصورة وعين شمس، وتم اعتماد الدراسة في بنائها النظري على نموذج قبول التكنولوجيا (TAM)، ونماذج جودة الخدمة (SQM)، توصلت الدراسة إلى العديد من النتائج من أهمها تنوع المنصات التعليمية التي تم استخدامها مع الطلاب أثناء جائحة كورونا، وجاء في مقدمتها Facebook ،Moodle ،zoom ،YouTube، وتنوعت المعايير المقترحة للتعليم عن بعد الخاص بالتعليم العالي في الجامعات المصرية، حيث تمثلت في القيادة - التقنية - التأهيل والدعم- العدالة وإمكانية الوصول- القياس والتقويم.
The current study aimed to identify the evaluation of faculty members in the field of media in Egyptian, universities of the quality of the educational process in higher education in light of the COVID-19 pandemic to identify the most important educational platforms that were used during the Corona pandemic, to monitor the challenges that were encountered while carrying out distance education, Reaching out to the formulation of proposed standards for distance education for higher education in Egyptian universities, The sample of the study was represented by professors of media at Cairo University, Mansoura and Ain Shams, and the study was based on its theoretical construction on the Technology Acceptance Model (TAM) and Service Quality Models (SQM), The study found many results, the most important of which is the diversity of the educational platforms that were used with students during the Corona pandemic, in the forefront of which was YouTube, zoom, Moodle, and Facebook, and the proposed criteria for distance education for higher education in Egyptian universities varied, as represented by leadership - technology - Rehabilitation and support - justice and access - measurement and evaluation.
Keywords: المؤسسات الأكاديمية -- العملية التعليمية -- التعليم العالي -- فيروس كرونا "كوفيد-19" -- التدابير الوقائية